Workplace violence against physicians in Turkey’s emergency departments: a cross-sectional survey - Başak Bayram; Murat Çetin; Neşe Çolak Oray; İsmail Özgür Can (BMJ Open)
Objective We aimed to determine the prevalence of violence directed at emergency department (ED) physicians in Turkey and confirm the factors influencing such violence.Design Cross-sectional survey study.Setting Country of Turkey.Participants Physicians currently practising in EDs in Turkey.Main outcome measures The prevalence of violence directed at physicians and factors that may influence it, such as physicians’ personal characteristics, ED characteristics and physicians’ opinions regarding the causes of and suggested methods of preventing violence.Results A total of 713 physicians participated. Of these, 78.1% reported being subjected to violence in the past year and 65.9% reported more than one such incident. Being subjected to violence was related to age (p=0.008), working in an ED with a high patient admission rate (p=0.018), current position (p<0.001), working outside regular work hours (p<0.001), working in a state hospital (p<0.001) and level of experience (p<0.001). Gender, type of patient typically seen, region and patient waiting period did not influence subjection to violence. The present safety precautions against violence do not appear to influence the prevalence of violence.Conclusions Our results indicated that ED physicians’ experience of violence is related to personal characteristics such as age and level of expertise, and hospital and ED characteristics such as high patient admission rates. Presently, no measures taken to reduce this violence have been proven effective.